STANDARDIZATION OF HIGHER EDUCATION AS A SCIENTIFIC AND PEDAGOGICAL ISSUE: THEORETICAL ANALYSIS - Illia Lysokon (Scientific Journal of Polonia University, 2023)
The standardization of higher education as a scientific and pedagogical issue is theoretically justified in the article. It has been established that the basis for the development of higher education standards and their adaptation, taking into account the European experience, are legislative acts that ensure the functioning of the sector of higher education in Ukraine, didactic materials and scientific intelligence on the subject of the phenomenon under study. The idea of the relationship between the quality of educational services in the system of higher education of Ukraine and the acceleration of educational reforms is highlighted. The theoretical and terminological aspect of the standardization of higher education was analysed, and the issue of replacing basic educational concepts was identified, which as a result leads to misunderstanding of the processes both in the education system and in its individual branches. Possible directions (globalization, Europeanization and intercultural one) of the educational policy of Ukraine for the development of higher education standards and their specifics are revealed. It was determined that the standardization of higher education and ensuring its quality takes place in the conditions of a liberal model of educational policy, which simultaneously strengthens the ideas of academic freedom and social responsibility of educational institutions. Therefore, the state educational policy of Ukraine sees the standardization of higher education as a tool for socio-cultural and economic growth.